Steroid Hormones in the Aquatic Environment – Review of the State of Knowledge and Comparison of Surface Water Pollution between Europe and Asia - Weselak, Marcin; Kaliszewicz, Anita (Studia Ecologiae et Bioethicae, 2025)
Steroid hormones are fundamental regulators of physiological processes in both animals and humans. The aim of this mini review is to present key findings in recent years regarding the presence and impact of steroid hormones on the natural environment. The high biological activity of individual steroid hormones combined with the absence of antagonistic effects when they occur simultaneously (e.g. in mixtures present in sewage) poses a significant threat to aquatic ecosystems in many water bodies. These compounds enter the aquatic environment through effluents of large livestock farms, industrial (pharmaceutical) plants and households. Over the past decade, concentrations of steroid hormones in European surface waters have increased significantly. Despite this, European countries have some of the cleanest surface waters in the world in terms of hormonal pollution. Nearly one-third of global emissions of animal-derived hormone pollutants are concentrated in India and Brazil, with India exhibiting the highest levels of anthropogenic steroid pollutant emissions. Even with removal efficiencies of 70–80%, wastewater treatment plants processing large water volumes discharge significant amounts of steroid hormones, which destabilise populations of many aquatic vertebrate and invertebrate species. Both Europe and Asia face serious threats to aquatic organisms from steroid hormones, but the nature and sources of this problem differ between regions.